بناء شخصيّة المرأة في القرآن الكريم - عبد العالى,أحمد (University of Eloued جامعة الوادي, 2023)
Abstract: In this study, we presented the character of women in the Holy Qur’an in description analysis and interpretation, by discussing some selected female characters and studying their psychological and sociological structures, We prepared for it by talking about Quranic stories in which the character is considered the most important component, starting from the sanctity and specificity of the divine speech and the miraculous manifestations therein, considering That he has characteristics that are unique from others, for he is the truth that is not tainted by falsehood and is not tainted by ambiguity or imagination, We later moved on to present the nature of the character in the Qur’anic stories, and then we tried to distinguish between the types of female characters studied, so we presented the character of Mary - peace be upon her - as a model of the devout, obedient woman. obedient to her Lord, and the character of Bilqis, Queen of Sheba, as a tongue for the queenly woman who manages the affairs of the king’s house well with wisdom and reason, and the character of the Aziz’s wife Zuleikha, as a model of the stubborn woman whose emotions prevail over her mind. Finally, we deduced some semantic and aesthetic dimensions for each of these female characters, highlighting the representations and behaviors of each, One of them and the secrets of its presence. تعرّضنا في هذه الدراسة لشخصيّة المرأة في القرآن الكريم وصفاً وتحليلاً وتفسيراً, من خلال التطرّق لبعض الشخوص النسائية المختارة ودراسة بنائَيها النفسي والسوسيولوجي, فمهّدنا له بالحديث عن القصص القرآني الذي تُعدّ الشخصيّة أهمّ مكوّناً من مكوّناته, منطلقين من قُدُسيّة وخصوصيّة الخطاب الربّاني ومظاهر الإعجاز فيه, باعتبار أنّ له صفات يتفرّد بها عن غيره, فهو الحقّ الذي لا يشوبه باطل ولا يعتريه غموض أو خيال, وانتقلنا فيما بعد لعرض ماهية الشخصيّة في القصص القرآني, ثمّ حاولنا التمييز بين أنماط الشخصيّات النسائية المدروسة، فعرضنا شخصيّة مريم _ عليها السلام _ كنموذج للمرأة العابدة القانتة والطائعة لربّها، وشخصية بلقيس ملكة سبأ لساناً للمرأة الملكة التي تُحسن إدارة شؤون بيت المُلك بحكمةٍ وتعقّل, وشخصية امرأة العزيز زُليخة كنموذج للمرأة العنيدة التي تغلِّب عواطفها على عقلها, في الأخير استنتجنا بعض الأبعاد الدّلالية والجمالية لكلّ شخصيّة من هذه الشخوص النسائية, مُبرزين تمثّلات وسلوكيّات كلّ واحدة منها وأسرار حضورها.
دراسة وصفيّة سيكولوجية لشخوص مختارة
Keywords: القصص القرآني; Structure; Psychology; Personality; Women; Quranic stories; The Holy Qura